Motor neuron translatome reveals deregulation of SYNGR4 and PLEKHB1 in mutant TDP-43 amyotrophic lateral sclerosis models. (7th July 2020) - Marques, Rita F; Engler, Jan B; Küchler, Katrin; Jones, Ross A; Lingner, Thomas; Salinas, Gabriela; Gillingwater, Thomas H; Friese, Manuel A; Duncan, Kent E
Abstract: Amyotrophic lateral sclerosis (ALS) is an incurable neurological disease with progressive loss of motor neuron (MN) function in the brain and spinal cord. Mutations in TARDBP, encoding the RNA-binding protein TDP-43, are one cause of ALS, and TDP-43 mislocalization in MNs is a key pathological feature of >95% of ALS cases. While numerous studies support altered RNA regulation by TDP-43 as a major cause of disease, specific changes within MNs that trigger disease onset remain unclear. Here, we combined translating ribosome affinity purification (TRAP) with RNA sequencing to identify molecular changes in spinal MNs of TDP-43–driven ALS at motor symptom onset. By comparing the MN translatome of hTDP-43 A315T mice to littermate controls and to mice expressing wild type hTDP-43, we identified hundreds of mRNAs that were selectively up- or downregulated in MNs. We validated the deregulated candidates Tex26, Syngr4, and Plekhb1 mRNAs in an independent TRAP experiment. Moreover, by quantitative immunostaining of spinal cord MNs, we found corresponding protein level changes for SYNGR4 and PLEKHB1. We also observed these changes in spinal MNs of an independent ALS mouse model caused by a different patient mutant allele of TDP-43, suggesting that they are general features of TDP-43-driven ALS. Thus, we identified SYNGR4 and PLEKHB1 to be deregulated in MNs at motor symptom onset in TDP-43-driven ALS models. This spatial and temporal pattern suggests that these proteins could be functionally important for driving the transition to the symptomatic phase of the disease.